Effect of monthly high‐dose vitamin D on bone density in community‐dwelling older adults substudy of a randomized controlled trial - Ian R. Reid; Anne Horne; Borislav Mihov; G. D. Gamble; F. Al‐Abuwsi; Mukesh Singh; Lynne Taylor; Sheryl Fenwick; Carlos A. Camargo; Alistair W. Stewart; Robert Scragg (2017)
Abstract Background Severe vitamin D deficiency causes osteomalacia, yet trials of vitamin D supplementation in the community have not on average demonstrated benefit to bone mineral density ( BMD ) or fracture risk in adults. Objective To determine whether monthly high‐dose vitamin D supplementation influences BMD in the general population and in those with low 25‐hydroxyvitamin D levels. Methods Two‐year substudy of a trial in older community‐resident adults. A total of 452 participants were randomized to receive monthly doses of vitamin D3 100 000 IU , or placebo. The primary end‐point was change in lumbar spine BMD . Exploratory analyses to identify thresholds of baseline 25‐hydroxyvitamin D for vitamin D effects on BMD were prespecified. Results Intention‐to‐treat analyses showed no significant treatment effect in the lumbar spine (between‐groups difference 0.0071 g cm −2 , 95% CI : −0.0012, 0.0154) or total body but BMD loss at both hip sites was significantly attenuated by ~1/2% over 2 years. There was a significant interaction between baseline 25‐hydroxyvitamin D and treatment effect ( P = 0.04). With baseline 25‐hydroxyvitamin D ≤ 30 nmol L −1 ( n = 46), there were between‐groups BMD changes at the spine and femoral sites of ~2%, significant in the spine and femoral neck, but there was no effect on total body BMD . When baseline 25‐hydroxyvitamin D was >30 nmol L −1 , differences were ~1/2% and significant only at the total hip. Conclusions This substudy finds no clinically important benefit to BMD from untargeted vitamin D supplementation of older, community‐dwelling adults. Exploratory analyses suggest meaningful benefit in those with baseline 25‐hydroxyvitamin D ≤ 30 nmol L −1 . This represents a significant step towards a trial‐based definition of vitamin D deficiency for bone health in older adults.